A species-specific double isotope dilution strategy for the accurate quantification of platinum–GG adducts in lung cells exposed to carboplatin. Issue 7 (28th June 2017) - Cuello-Nuñez, Susana; Larios, Raquel; Deitrich, Christian; Lekishvili, Tamara; Nischwitz, Volker; Sharp, Barry L.; Goenaga-Infante, Heidi
Abstract : Measurement uncertainty of Pt–GG quantification in human lung cells by species-specific double IDMS. Abstract : Platinum–DNA adducts, and in particular Pt–GG, have been identified as the major cytotoxic species during chemotherapy treatment with platinum containing drugs. This paper reports for the first time a strategy based on the use of double species-specific isotope dilution analysis (IDA) for the quantification of carboplatin–GG adducts formed by exposing human lung carcinoma cells to carboplatin. The main challenge posed by the use of carboplatin in this pre-clinical application, in comparison with most previously reported studies using cisplatin, includes the relatively low reactivity of this drug, thus demanding for improved limits of detection to be achieved in order to perform accurate quantification of the adducts at low ng Pt per mg DNA levels with relatively small uncertainty in micro-volumes of the biological sample. This was alleviated by developing micro-flow HPLC reversed phased methodology coupled to sector field ICP-MS ( R = 300), showing a limit of detection of 0.2 ng Pt per mg DNA. To perform IDA, carboplatin–GG calibrants and spikes ( 194 Pt-enriched GG adducts) were synthesized in house and characterised for Pt mass fraction, Pt distribution and structural composition. In order to assess the accuracy of the developed procedure, in the absence of certified reference materials, a reference sample prepared by incubation of calf thymus DNA with carboplatin and characterised in house ( e.g. for its total P and Pt contents and Pt–GG concentration) was analysed in parallel. The use of this sample as a quality control of the cleavage of DNA and recovery of Pt adducts from real samples makes the described strategy particularly novel. Moreover, spike recovery experiments on the cell samples with the reference carboplatin–DNA sample were undertaken. The validated methodology was applied to cultured human lung carcinoma cells exposed to carboplatin; Pt–GG adducts were found to be at a level of 5.54 ng Pt per mg DNA with a relatively expanded combined uncertainty ( k = 2) of approximately 20%. The major contributing factors to the overall measurement uncertainty were the mass fraction of Pt in the natural carboplatin–GG standard, the measured isotope ratio precision of sample and calibration blends and the blend to blend variation. The SI traceable methodology presented here will be invaluable for the provision of reference values to clinical measurements and cancer clinical trials.